Analysis of the need to develop e-modules for explanatory texts on disaster mitigation literacy in schools affected by the Lembang Fault - Fikri Azis Makrus; Yeti Mulyati; Khaerudin Kurniawan (Universitas Muhammadiyah Malang, 2026)
Teaching explanatory texts in schools located in earthquake-prone areas requires digital teaching materials that not only strengthen literacy competencies but also equip students with a contextual understanding of disaster mitigation. However, the availability of contextual, structured, and interactive e-modules remains limited, particularly those that link the material to the conditions of the Lembang Fault zone. This study aims to analyze the needs of teachers and students for the development of explanatory text e-modules incorporating disaster mitigation literacy. The study employs a qualitative descriptive approach. The data sources comprise 25 Indonesian-language teachers and 86 junior high school students from five schools in the Lembang Fault zone. Data were collected through questionnaires administered to teachers and students, interviews, and a documentary study of the teaching materials used in schools. Data analysis was conducted thematically through reduction, presentation, and conclusion drawing, using source triangulation. The results indicate that the teaching materials used are still dominated by printed books, and the utilization of digital teaching materials remains uneven; teachers and students emphasized the importance of e-modules that integrate local disaster-related content; e-modules need to have a systematic and clear learning structure, case-based activities, and a focus on strengthening disaster mitigation competencies; and interactive digital features are considered essential for enhancing student engagement in learning. This study concludes that explanatory e-modules on disaster mitigation literacy should be designed in a contextual, systematic, and interactive manner to address learning needs and strengthen student preparedness in earthquake-prone areas.